Game on : energize your business with social media games - Radoff, Jon. (Indianapolis, IN : Wiley Publishing, Inc., 2011)
Social media games satisfy the need to interact, compete and exercise imagination, plus they're fun. What if your business offered those rewards to your customers? Consider looking at your business as if it were a game -- discover how fun can generate energy that boosts the bottom line.
Understanding social games: How to play this book ; Games have changed the business playfield ; Developing social media games -- customers as players ; Fungineering ; Turning work into fun -- Designing social games: Anatomy of a social game ; Understanding social game business models ; Using storytelling to understand your design objectives ; Creating compelling game systems ; Designing game interfaces ; Designing for virtual goods ; coda -- Glossary ; Resource guide ; Book references ; Index.
Includes bibliographical references (p. [365]-370) and index.
Keywords: Internet marketing; Social media -- Economic aspects; Online social networks -- Economic aspects; Social media -- Games; Social networks -- Games; Marketing -- Social aspects -- Games; Internet marketing; Social networking -- Economic aspects; Internet games